Pelvic floor dysfunction in female patients at two academic hospitals in Johannesburg, three months post-pelvic fracture - Chopdat, Nazreen (University of the Witwatersrand, Johannesburg, 2024)
Background: Research is sparse on PFD* in females who sustained a pelvic fracture in South Africa. This study aimed to determine PFD symptoms and associated factors among females aged 18 years three months post-pelvic fracture Method: A three-month quantitative longitudinal study was conducted over 19 months, at two South African teaching hospitals. History obtained from medical records and patient questioning; APFQ* used for PFD symptoms. Correlation tests and linear regression analysis were used. Results: Of 44 participants recruited, 37 completed the three-month follow-up. Median age was 37 (interquartile range 30.5-58) years. PVA* accounted for 87.50% of multiple fractures (P=0.040). Bladder and bowel dysfunction were most common, with sexual avoidance a significant outcome following pelvic trauma. The injury directly or indirectly limited sexual activity in 45.45% participants. Significant changes were noted in Total (p=0.0216), Bladder (p=0.0062) and Sexual (p=0.0087) domain APFQ scores from preinjury to three months post-injury; and between subacute and three months post-injury, APFQ* Total (p=0.0361), Bladder (p=0.0002) and Bowel (p<0.0001) domain scores. Prolonged urinary catheter use, increased risk for higher scores of bladder PFD* (n=37, r=0.1585). Factors associated with less PFD at three months included number of vaginal deliveries preinjury (p-value 0.026, coeff -2.77, (95%CI: - 5.17 to -0.36), and bedrest with non-weightbearing choice of treatment (p-value 0.046, coeff -4.00, 95% CI: -7.92 to -0.08). Conclusion: PFD is present prior to and at three months post pelvic fracture with an increase in frequency and severity at three months. Symptoms are most prevalent in the subacute phase. The results of this study support the relevance of screening for PFD* within the early period and at three months for females following orthopaedic trauma. Clinical implications: Screening for PFD should become standard practice for females’ post-pelvic fracture in hospital and during outpatient follow-ups. Duration of catheterisation should be justifiable. Screening for bladder dysfunction is pertinent in patients requiring prolonged catheterisation, and patients requiring less conservative management. Guidance on safety to return to sexual activity is important to include as vi part of routine follow-up orthopaedic sessions. Integrating PFD screening and management into standard orthopaedic practice can improve outcomes and quality of life of affected individuals.
A research report submitted in fulfillment of the requirements for the Master of Science in Physiotherapy, in the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Pelvic fractures; Pelvic floor dysfunction; Female pelvic fractures; Australian pelvic floor questionnaire; Orthopaedic Management; Physiotherapy; South Africa; Screening; Early intervention; PFD; Trauma; SDG-3: Good health and well-being